Times Higher Education World University Rankings for 2012-2013 and Prospects for Science Development in Armenia - Harutyunyan, T. (Science and Innovation, 2024)
The paper covers Times Higher Education World Universities Rankings and the criteria, according to which these universities have been included therein. Most of them are located in North America and in Europe and represent the Anglo-Saxon school. In the list of top universities there have appeared more and more Asian universities of technical and natural science as a result of an increase in the number of research universities. The possibilities to establish a research university in Armenia, as well as the circumstances that can facilitate or impede the achievement of this goal have been considered. The megaprojects implemented in Armenia are presented and the role of research universities in promotion and establishment of these projects is described.